Pengaruh Compensation dan Motivation terhadap Employee Performance (Studi Kasus pada CV Sumber Milik Farm) - Mariati Tirta Wiyata; Frandi Haryanto (Cakrawala Repositori IMWI, 2018)
This study aims to determine: (1) the effect of compensation on employee performance, (2) the influence of motivation on employee performance, and (3) the influence of compensation and motivation simultaneously on employee performance. The subject of this research is all employees CV SumberMilik Farm Sukabumi. The number of respondents in this study as many as 80 people. Methods of data collection through survey by using questionnaire. Data analysis technique used in this research is Multiple Linear Regression Analysis. The results showed that (1) the compensation positively affects the employee's performance with a value of 2.252 > 1.66515 and a significance value of 0.027 < 0.05; (2) motivation positively influence to employee performance with value 5,439 > 1,66515 and significance value 0,000 < 0,05; (3) simultaneously compensation and motivation positively affect employee performance with score 38,203 > 3,12 and significance value 0,000 < 0,05